Preparation method and application of hydroxyapatite modified biochar

CN122912807APending Publication Date: 2026-10-16GUANGXI INST OF BOTANY THE CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611391610.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-09
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种羟基磷灰石改性生物炭的制备方法及应用,解决了现有羟基磷灰石改性生物炭制备工艺中,无机前驱体容易在生物质外表面提前发生非均相沉淀,导致有效活性组分分布不均以及内部孔隙堵塞,且常规负载的无机相在动态水处理环境中容易受流体剪切力作用发生脱落流失;常规热解工艺制得的生物炭孔隙结构发育不充分,比表面积偏低,表面缺乏相应的络合吸附位点,从而限制了材料对重金属等污染物的环境净化效能的问题

Benefits of technology

1、本发明通过聚磷酸铵的配位掩蔽作用与负压诱导闪蒸结晶技术的结合,改善了无机有效组分在生物炭上的分布状态。聚磷酸铵在常温下与钙离子发生配位,抑制了无机前驱体在生物质外表面的非均相沉淀;在密闭加热与随后的瞬态压降过程中,体系内溶解氨气的快速相变脱除诱发了羟基磷灰石在微观孔道内部的均相结晶成核。这一过程有效减轻了粗大无机颗粒对外层孔道的物理堵塞,提高了有效活性相在材料深层孔隙中的分散均匀性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912807A_ABST
    Figure CN122912807A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of water pollution prevention and control materials, and discloses a preparation method and application of hydroxyapatite modified biochar, which comprises the following steps: mixing and impregnating ammonium polyphosphate, calcium acetate and biomass, and using macromolecular coordination to mask calcium ions; adding urea, sealing, increasing temperature and maintaining pressure, realizing synchronous hydrolysis of components and maintaining buffer; then performing negative pressure suction flash evaporation pressure relief, inducing hydroxyapatite to instantaneously nucleate in the deep pore channel of the biomass, and simultaneously pressurizing and storing the discharged mixed gas; after solid-liquid separation, performing anaerobic heating carbonization, using skeleton contraction to mechanically embed the inorganic phase; finally, using the stored mixed gas to perform gas phase jet quenching activation on the high-temperature carbonized material, realizing in-situ pore forming and surface amination. The application effectively improves the problems of inorganic phase agglomeration and falling off and low specific surface area of biochar, the obtained material is developed in pores and firmly combined, and has excellent adsorption and purification efficiency in water pollution prevention and control.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water pollution control materials technology, specifically to a method for preparing hydroxyapatite-modified biochar and its application. Background Technology

[0002] With the continuous advancement of industrialization, the prevention and control of heavy metal pollution in water bodies has increasingly attracted attention in the field of environmental engineering. Developing water pollution control agents that are both economical and highly efficient has become an important research topic. Biochar, due to its wide availability and porous structure, is often used as an adsorption substrate for water treatment. To further enhance its ability to remove pollutants such as heavy metals, hydroxyapatite, which has good environmental compatibility, has been introduced for modification.

[0003] In existing processes for preparing hydroxyapatite-modified biochar, companies and research institutions typically employ conventional liquid-phase co-precipitation or simple mixed pyrolysis methods. During this process, the biomass substrate is immersed in a precursor solution containing calcium salts and phosphates. Subsequently, alkaline reagents such as ammonia or sodium hydroxide are added externally to forcibly alter the pH of the system, promoting the formation and adhesion of hydroxyapatite onto the substrate. Some processes also involve drying the phosphorus-calcium precursor biomass and then directly feeding it into a kiln for high-temperature carbonization. The resulting modified biochar material is then packed into a fixed-bed adsorption tower or reaction vessel as an adsorbent for treating flowing water. The heavy metal wastewater is treated by the physical pores of the carbon substrate and the surface-loaded inorganic phase, which together trap and retain the pollutants.

[0004] However, during liquid-phase precipitation, the external addition of alkaline solution can cause local concentration imbalances within the reaction system. Due to the lack of effective masking for free calcium ions, inorganic precursors undergo rapid heterogeneous precipitation on the outer surface of biomass, leading to the accumulation of coarse particles and scaling on the outer layer. This clogs the original vascular bundles and micropores within the biomass, increasing the mass transfer resistance for heavy metal ions to diffuse deeper into the material. Inorganic particles generated by conventional methods often adhere to the carbon surface through weak physical interactions such as electrostatic adsorption. Under continuous influent conditions in dynamic water treatment, the inorganic phase, lacking depth confinement and mechanical interlocking, is unable to resist the long-term physical erosion of water flow and is prone to peeling and detachment. This not only reduces the adsorption capacity of the reagents but also increases the turbidity of the effluent. Therefore, this invention provides a method for preparing hydroxyapatite-modified biochar and its application to address the shortcomings of existing technologies. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for preparing hydroxyapatite-modified biochar and its application. This method solves the problems in existing hydroxyapatite-modified biochar preparation processes, such as the tendency for inorganic precursors to prematurely precipitate heterogeneously on the outer surface of biomass, leading to uneven distribution of effective active components and internal pore blockage. Furthermore, conventionally loaded inorganic phases are easily detached and lost under fluid shear forces in dynamic water treatment environments. Additionally, biochar prepared by conventional pyrolysis processes suffers from insufficient pore structure development, low specific surface area, and a lack of corresponding complexation adsorption sites, thus limiting the material's environmental purification efficiency for pollutants such as heavy metals.

[0006] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a method for preparing hydroxyapatite-modified biochar, employing the following technical solution: A method for preparing hydroxyapatite-modified biochar includes the following steps: Step S1: Mix deionized water, biomass, ammonium polyphosphate and calcium acetate, and stir and impregnate under constant temperature to obtain impregnation slurry; Step S2: Add urea to the impregnation slurry and perform a heating and pressure treatment under closed conditions to form and maintain an absolute pressure in a slightly positive pressure state within the reaction system. Step S3: Depressurize the reaction system after pressure holding treatment, and simultaneously introduce power steam for negative pressure suction to reduce the pressure in the reaction system to atmospheric pressure. Then, pressurize the pumped mixed gas and send it to a heat-insulated high-pressure buffer tank for sealed constant temperature buffering. Step S4: Discharge the bottom slurry in the depressurized reaction system and perform solid-liquid separation to obtain wet precursor material; Step S5: The wet precursor material is heated and carbonized in an oxygen-free atmosphere to obtain solid carbonized material; Step S6: Place the solid carbon material in a sealed discharge chamber, introduce the mixed gas containing ammonia and water vapor that was extracted, discharged and pressurized in step S3, and directly spray the solid carbon material through a gas phase jet to perform quenching and activation treatment. After cooling, hydroxyapatite modified biochar is obtained.

[0007] By adopting the above technical solution, this invention combines physical phase transformation with multiphase chemical reaction during the preparation process, which is beneficial for obtaining modified materials with stable structure and high specific surface area. The relevant reaction process and principle are as follows: During the impregnation stage, ammonium polyphosphate is used as a macromolecular phosphorus source. The linear polyphosphoric groups of ammonium polyphosphate have a spatial coordination effect on calcium ions, which can mask free calcium ions in the liquid phase. This coordination effect helps to inhibit the heterogeneous precipitation of calcium ions and phosphorus source at room temperature, thereby providing a relatively stable precursor impregnation solution, which facilitates the inorganic precursor to penetrate into the deep pores of biomass through capillary action.

[0008] During the heating and pressurization stage, a multi-component simultaneous hydrolysis reaction occurs within the system. Ammonium polyphosphate undergoes chain scission hydrolysis upon heating, releasing orthophosphate ions. Urea undergoes thermal hydrolysis to produce ammonia, which reacts with carbon dioxide in the following reaction: Because the system is in a closed state and a slight positive pressure is formed inside, most of the generated ammonia gas remains in the liquid phase, which allows the system to maintain a certain buffer state. This slight pressure buffer environment helps to delay the premature nucleation of hydroxyapatite at high temperatures, and constructs a metastable liquid phase rich in calcium ions and orthophosphate in the deep pores of biomass.

[0009] During the negative pressure suction stage, the reaction system experiences a transient pressure drop, disrupting the original gas-liquid phase equilibrium. The dissolved ammonia undergoes a rapid phase transition and is removed, causing a transient increase in the pH of the liquid environment within the pores. This change in pH promotes homogeneous crystallization and nucleation of hydroxyapatite in the highly supersaturated regions within the micropores, as shown in the reaction equation. The instantaneous homogeneous crystallization process alleviates the local concentration gradient caused by conventional dropping methods, which is conducive to the relatively uniform distribution of inorganic phase in deep pores and reduces pore blockage to a certain extent.

[0010] During the heating and carbonization stage, biomass undergoes thermal dehydration and aromatization reactions, resulting in a volume shrinkage of its macroscopic structure. Hydroxyapatite particles grown in situ within the pores are densified and shrink under the influence of the amorphous carbon framework, facilitating the formation of a mechanically interlocked state in space. This spatially confined structure of the carbon substrate and the inorganic phase helps increase the bonding strength of the material, thereby improving its ability to resist external fluid shear forces during water treatment.

[0011] During the quenching and activation stage, a mixed gas containing ammonia and water vapor, collected and pressurized in the previous process, is used as an activation medium to impact the high-temperature solid-phase carbonized material. The water vapor undergoes an endothermic water-gas conversion reaction with the high-temperature carbon surface; the corresponding reaction formula is as follows. The chemical ablation process helps to expand the pore volume of the material, thereby increasing the specific surface area of ​​the product. Simultaneously, the ammonia in the mixed gas undergoes a gas-phase thermal dissociation reaction on the carbon substrate surface, enabling the grafting of nitrogen-containing functional groups onto the carbon framework. The strong endothermic nature of the gas-solid reaction consumes the heat of the material, thus cooling the high-temperature material.

[0012] Preferably, in steps S1 and S2, the raw materials include, by mass parts: 800-1200 parts of deionized water, 100-150 parts of biomass, 15-30 parts of ammonium polyphosphate, 25-50 parts of calcium acetate, and 60-100 parts of urea.

[0013] By adopting the above technical solution, it is helpful to maintain the metering balance of materials in the reaction system, and provide a suitable concentration of polymer coordination chain length and sufficient hydrolysis gas source for the reaction.

[0014] Preferably, the biomass is any one of pine sawdust, bamboo powder, corn stalks or rice stalks; the ammonium polyphosphate is a linear water-soluble inorganic polymer with a degree of polymerization in the range of 20 to 50.

[0015] By adopting the above technical solution, a porous carbon precursor with a corresponding vascular bundle pore structure is provided. Ammonium polyphosphate with a specific degree of polymerization can better balance water solubility and macromolecular coordination masking ability.

[0016] Preferably, in step S1, the initial temperature is controlled at 20-25°C, the stirring speed is set at 150-250 r / min, and the constant temperature impregnation time is 1.5-2.5 h; the addition ratio of ammonium polyphosphate and calcium acetate satisfies the molar ratio of calcium to phosphorus in the system being 1.60:1-1.70:1.

[0017] By adopting the above technical solution, suitable fluid diffusion kinetic conditions were set, which is conducive to the penetration of macromolecular complexes into deep pores. The set calcium-phosphorus molar ratio basically meets the stoichiometric requirements of the hydroxyapatite standard crystal phase.

[0018] Preferably, in step S2, the heating rate is controlled at 1.5 to 2.5 °C / min, the slurry temperature is raised to 105 to 110 °C, and the mixture is stirred at a constant temperature of 105 to 110 °C for 2.0 to 3.0 h; the absolute pressure of the micro-positive pressure state is 0.15 to 0.20 MPa.

[0019] By adopting the above technical solution, the reaction rate of simultaneous hydrolysis of components is well controlled, and the high solubility condition of liquid ammonia is constructed by relying on self-generated pressure, which helps to maintain the metastable buffer environment required for nucleation.

[0020] Preferably, in step S3, motive steam with a pressure of 0.6 to 0.8 MPa is introduced as an ejector source, and the pressure in the reaction system is controlled to drop to 0.1 MPa within 3 to 5 seconds; the mixed gas extracted and discharged is mixed with the motive steam and then pressurized to an absolute pressure of 0.30 to 0.40 MPa; the internal temperature of the heat-insulated high-pressure buffer tank is controlled by electric heating within the range of 145 to 155°C.

[0021] By adopting the above technical solution, a rapid pressure drop was achieved using the ejector source, providing a corresponding driving force for instantaneous crystal nucleation. Temperature control helps maintain the superheated vapor phase when the mixed gas is stored in the buffer tank, reducing the impact of condensation and pressure loss.

[0022] Preferably, in step S4, a plate and frame filter press is used for solid-liquid separation, and the filter cake is pressed until the moisture content reaches 40% to 50%.

[0023] By adopting the above technical solution, excess free water is removed while retaining some of the water-containing structures inside the pores, providing a relatively stable wet material basis for the subsequent carbonization and pore-forming stages.

[0024] Preferably, in step S5, nitrogen is introduced to maintain an oxygen-free atmosphere inside the kiln, the heating rate is controlled at 8-12℃ / min, the temperature is raised to 500-600℃, and constant temperature pyrolysis is performed at 500-600℃ for 1.5-2.5h; the volatile gases produced by pyrolysis are led to the post-combustion chamber for combustion.

[0025] By adopting the above technical solution, the biomass is induced to complete carbonization and shrinkage. The gas generated by the thermal decomposition of calcium acetate provides a primary physical expansion and pore-forming effect, and the inert atmosphere can reduce the excessive oxidation and burn-off of the carbon skeleton.

[0026] Preferably, in step S6, the mixed gas is transported to the sealed discharge chamber by utilizing the gas pressure difference of 0.30 to 0.40 MPa in the heat-insulated high-pressure buffer tank, and the solid carbonized material bed is sprayed through the atomizing nozzle to form a gas phase jet, and the contact time is controlled to be 10 to 20 minutes.

[0027] By adopting the above technical solution, high-pressure jetting enhances the gas-solid two-phase mass transfer process, which helps the water-gas reaction and gas-phase amination reaction to proceed fully within the set contact time, thereby promoting the expansion of material pores and the grafting of surface functional groups.

[0028] Secondly, this invention provides an application of hydroxyapatite-modified biochar, employing the following technical solution: Application of hydroxyapatite-modified biochar prepared by the above method in water pollution control agents.

[0029] By adopting the above technical solution, the modified biochar is applied to water pollution prevention and control. The material utilizes a relatively well-developed microporous network for physical interception, utilizes a deeply mechanically integrated and shear-resistant hydroxyapatite phase for chemical precipitation, and combines with the amino functional groups on the surface for Lewis acid-base complexation, thereby achieving comprehensive adsorption and removal of heavy metal ions in water to a certain extent.

[0030] This invention provides a method for preparing hydroxyapatite-modified biochar and its application. It has the following beneficial effects: 1. This invention improves the distribution of inorganic active components on biochar by combining the coordination masking effect of ammonium polyphosphate with negative pressure-induced flash crystallization technology. At room temperature, ammonium polyphosphate coordinates with calcium ions, inhibiting heterogeneous precipitation of inorganic precursors on the outer surface of biomass. During closed heating and subsequent transient pressure drop, the rapid phase transition removal of dissolved ammonia in the system induces homogeneous crystallization and nucleation of hydroxyapatite within the micropores. This process effectively reduces the physical blockage of outer pores by coarse inorganic particles and improves the uniformity of the effective active phase dispersion in the deep pores of the material.

[0031] 2. In this invention, hydroxyapatite crystals are pre-nucleated and grown within the deep pores of the biomass. During the subsequent high-temperature carbonization stage, the biomass substrate undergoes macroscopic volume shrinkage due to thermal dehydration and aromatization. The shrunken amorphous carbon skeleton spatially confines and encapsulates the inorganic particles within the pores, forming a relatively tight mechanical interlocking state. This allows the inorganic active phase to better resist the erosion caused by water flow shear forces, reducing the loss rate of effective components.

[0032] 3. In this invention, water vapor in the mixed gas undergoes a water-gas conversion reaction with the high-temperature carbon skeleton, increasing the micropore volume and specific surface area of ​​the product through chemical ablation. Simultaneously, ammonia undergoes gas-phase dissociation at high temperature, grafting nitrogen-containing functional groups onto the carbon surface. This step, while recovering and utilizing process gases, increases the physical retention space and chemical complexation sites for heavy metal ions in the material, thereby improving the overall adsorption efficiency of the material. Attached Figure Description

[0033] Figure 1 This is a schematic diagram of the phase and surface chemistry of Test Example 1 of the present invention, wherein (a) is the X-ray diffraction pattern of Example 1 and Comparative Example 3, and (b) is the high-resolution N 1s X-ray photoelectron spectrum of Example 1 and Comparative Example 5. Figure 2 This is the nitrogen adsorption-desorption isotherm diagram of the present invention; Figure 3 This is a graph showing the turbidity of the effluent as a function of flushing time according to the present invention. Figure 4 This is a graph showing the lead ion adsorption kinetics of the present invention. Detailed Implementation

[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0035] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0036] Pine wood chips, bamboo powder, corn stalks, and rice straw are all commercially available biomass products. Before use, they are mechanically crushed and sieved to 20-40 mesh, and then dried to constant weight in a forced-air drying oven for later use.

[0037] Ammonium polyphosphate has the CAS number 68333-79-9 and the chemical formula (NH4PO3). n This is a linear inorganic polymer composed of multiple phosphate groups linked by oxygen atoms to form the main chain. The repeating structural unit of this ammonium polyphosphate is -PO3(NH4)-, and its degree of polymerization (n) ranges from 20 to 50, corresponding to a number-average molecular weight range of 1940 g / mol to 4850 g / mol. This specification of polymer is a water-soluble short-chain polymer, with a solubility greater than 20 g / 100 mL in deionized water at 20°C. It is a commercially available industrial-grade product.

[0038] The CAS number for calcium acetate is 62-54-4. It is a commercially available industrial-grade anhydrous product with a purity greater than or equal to 98.0 wt%.

[0039] The CAS number of urea is 57-13-6. It is a commercially available industrial-grade product with a purity greater than or equal to 99.0 wt%.

[0040] Deionized water is a commercially available industrial-grade product with a conductivity of less than or equal to 0.1 μS / cm at room temperature.

[0041] The CAS number of diammonium hydrogen phosphate is 7783-28-0. It is a commercially available industrial-grade anhydrous product with a purity greater than or equal to 98.0 wt%.

[0042] The CAS number for calcium nitrate is 10124-37-5. It is a commercially available industrial-grade anhydrous product with a purity greater than or equal to 99.0 wt%.

[0043] Preparation Example 1: This preparation example provides a method for preparing a composite precursor impregnation slurry, including the following steps: 1000 parts of deionized water and 120 parts of pine sawdust were added to a pressure-resistant stirred reactor with a heating jacket. The initial temperature of the system was controlled at 22℃. 18 parts of ammonium polyphosphate and 49 parts of calcium acetate were added sequentially. The molar ratio of calcium to phosphorus in the system was calculated to be 1.67. The mechanical stirring in the reactor was turned on and the stirring speed was set to 200 r / min. The mixture was kept at 22℃ for 2.0 h to obtain the composite precursor impregnation slurry.

[0044] Preparation Example 2: This preparation example provides a method for preparing a composite precursor impregnation slurry, including the following steps: 800 parts of deionized water and 100 parts of corn stalks were added to a pressure-resistant stirred reactor with a heating jacket. The initial temperature of the system was controlled at 20℃. 15 parts of ammonium polyphosphate and 39 parts of calcium acetate were added sequentially. The molar ratio of calcium to phosphorus in the system was calculated to be 1.60. The mechanical stirring in the reactor was turned on and the stirring speed was set to 150 r / min. The mixture was kept at 20℃ for 1.5 h to obtain the composite precursor impregnation slurry.

[0045] Preparation Example 3: This preparation example provides a method for preparing a composite precursor impregnation slurry, including the following steps: 1200 parts of deionized water and 150 parts of rice straw were added to a pressure-resistant stirred reactor with a heating jacket. The initial temperature of the system was controlled at 25℃. 18 parts of ammonium polyphosphate and 50 parts of calcium acetate were added sequentially. The molar ratio of calcium to phosphorus in the system was calculated to be 1.70. The mechanical stirring in the reactor was turned on and the stirring speed was set to 250 r / min. The mixture was kept at 25℃ for 2.5 h to obtain the composite precursor impregnation slurry.

[0046] Example 1:

[0047] This embodiment provides a method for preparing hydroxyapatite-modified biochar, including the following steps: Step S1: Add 1000 parts of deionized water and 120 parts of pine wood chips to a pressure-resistant stirred reactor with a heating jacket. Control the initial temperature of the system to 22°C. Add 18 parts of ammonium polyphosphate and 49 parts of calcium acetate in sequence. Turn on the mechanical stirring in the reactor and set the stirring speed to 200 r / min. Soak at a constant temperature of 22°C for 2.0 h.

[0048] Step S2: Add 80 parts of urea to the reactor, seal the reactor body and all exhaust valves; introduce a heat source into the reactor jacket, control the heating rate to 2.0℃ / min, raise the temperature of the slurry in the reactor to 108℃, and stir at 108℃ for 2.5h. During this closed heating process, an absolute pressure of 0.18MPa is formed and maintained inside the reactor.

[0049] Step S3: Stop the heating of the reactor jacket, fully open the pneumatic pressure relief valve at the top of the reactor, and simultaneously start the steam jet compressor connected to the pipeline. Introduce 0.7MPa of motive steam as the injection source, and control the pressure inside the reactor to drop to 0.1MPa within 4 seconds. The mixed gas discharged from the reactor pressure relief is drawn in by the ejector and mixed with the motive steam. The mixed fluid is pressurized to an absolute pressure of 0.35MPa. The pressurized mixed gas is discharged into the heat-insulated high-pressure buffer tank for sealed buffering. The internal temperature of the heat-insulated high-pressure buffer tank is controlled at 150℃ by electric heating.

[0050] Step S4: Discharge the slurry from the bottom of the reactor after treatment and pump it into an industrial plate and frame filter press for solid-liquid separation. Press the filter cake until the moisture content reaches 45% to obtain the wet precursor material.

[0051] Step S5: Feed the wet precursor material into the rotary kiln, introduce nitrogen to maintain an oxygen-free atmosphere inside the kiln, control the heating rate to 10℃ / min, raise the kiln temperature to 550℃, and pyrolyze at 550℃ for 2.0h. The volatile gases produced by pyrolysis are led to the combustion chamber after the rotary kiln for incineration.

[0052] Step S6: After pyrolysis, stop heating the rotary kiln and push the solid carbonized material at 550℃ into the sealed quenching discharge chamber at the tail of the rotary kiln. Fully open the gas outlet valve of the heat-insulating high-pressure buffer tank and use the gas pressure difference of 0.35MPa in the tank to transport the pressurized mixed gas to the quenching discharge chamber. Form a gas phase jet through the atomizing nozzle and directly spray it onto the solid carbonized material bed. Control the contact time to 15 minutes. The generated tail gas is discharged into the combustion chamber. After the solid material is cooled to room temperature, it is discharged to obtain hydroxyapatite modified biochar.

[0053] Example 2:

[0054] This embodiment provides a method for preparing hydroxyapatite-modified biochar, including the following steps: Step S1: Add 800 parts of deionized water and 100 parts of corn stalks to a pressure-resistant stirred reactor with a heating jacket. Control the initial temperature of the system to 20°C. Add 15 parts of ammonium polyphosphate and 39 parts of calcium acetate in sequence. Turn on the mechanical stirring in the reactor and set the stirring speed to 150 r / min. Soak at a constant temperature of 20°C for 1.5 h.

[0055] Step S2: Add 60 parts of urea to the reactor, seal the reactor body and all exhaust valves; introduce a heat source into the reactor jacket, control the heating rate to 1.5℃ / min, raise the temperature of the slurry in the reactor to 105℃, and stir at 105℃ for 2.0h. During this closed heating process, an absolute pressure of 0.15MPa is formed and maintained inside the reactor.

[0056] Step S3: Stop the heating of the reactor jacket, fully open the pneumatic pressure relief valve at the top of the reactor, and simultaneously start the steam jet compressor connected to the pipeline. Introduce 0.6MPa of motive steam as the injection source, and control the pressure inside the reactor to drop to 0.1MPa within 3 seconds. The mixed gas discharged from the reactor pressure relief is drawn in by the ejector and mixed with the motive steam. The mixed fluid is pressurized to an absolute pressure of 0.30MPa. The pressurized mixed gas is discharged into the heat-insulated high-pressure buffer tank for sealed buffering. The internal temperature of the heat-insulated high-pressure buffer tank is controlled at 145℃ by electric heating.

[0057] Step S4: Discharge the slurry from the bottom of the reactor after treatment and pump it into an industrial plate and frame filter press for solid-liquid separation. Press the filter cake until the moisture content reaches 40% to obtain the wet precursor material.

[0058] Step S5: Feed the wet precursor material into the rotary kiln, introduce nitrogen to maintain an oxygen-free atmosphere inside the kiln, control the heating rate to 8℃ / min, raise the kiln temperature to 500℃, and pyrolyze at 500℃ for 1.5h. The volatile gases produced by pyrolysis are led to the combustion chamber after the rotary kiln for incineration.

[0059] Step S6: After pyrolysis, stop heating the rotary kiln and push the solid carbonized material at 500℃ into the sealed quenching discharge chamber at the tail of the rotary kiln. Fully open the gas outlet valve of the heat-insulating high-pressure buffer tank and use the gas pressure difference of 0.30MPa in the tank to transport the pressurized mixed gas to the quenching discharge chamber. Form a gas phase jet through the atomizing nozzle and directly spray it onto the solid carbonized material bed. Control the contact time to 10 minutes. The generated tail gas is discharged into the combustion chamber. After the solid material is cooled to room temperature, it is discharged to obtain hydroxyapatite modified biochar.

[0060] Example 3:

[0061] This embodiment provides a method for preparing hydroxyapatite-modified biochar, including the following steps: Step S1: Add 1200 parts of deionized water and 150 parts of rice straw to a pressure-resistant stirred reactor with a heating jacket. Control the initial temperature of the system to 25°C. Add 18 parts of ammonium polyphosphate and 50 parts of calcium acetate in sequence. Turn on the mechanical stirring in the reactor and set the stirring speed to 250 r / min. Soak at a constant temperature of 25°C for 2.5 h.

[0062] Step S2: Add 100 parts of urea to the reactor, seal the reactor body and all exhaust valves; introduce a heat source into the reactor jacket, control the heating rate to 2.5℃ / min, raise the temperature of the slurry in the reactor to 110℃, and keep it at 110℃ for 3.0h. During this closed heating process, an absolute pressure of 0.20MPa is formed and maintained inside the reactor.

[0063] Step S3: Stop the heating of the reactor jacket, fully open the pneumatic pressure relief valve at the top of the reactor, and simultaneously start the steam jet compressor connected to the pipeline. Introduce 0.8MPa of motive steam as the injection source, and control the pressure inside the reactor to drop to 0.1MPa within 5 seconds. The mixed gas discharged from the reactor pressure relief is drawn in by the ejector and mixed with the motive steam. The mixed fluid is pressurized to an absolute pressure of 0.40MPa. The pressurized mixed gas is discharged into the heat-insulated high-pressure buffer tank for sealed buffering. The internal temperature of the heat-insulated high-pressure buffer tank is controlled at 155℃ by electric heating.

[0064] Step S4: Discharge the slurry from the bottom of the reactor after treatment and pump it into an industrial plate and frame filter press for solid-liquid separation. Press the filter cake until the moisture content reaches 50% to obtain wet precursor material.

[0065] Step S5: Feed the wet precursor material into the rotary kiln, introduce nitrogen to maintain an oxygen-free atmosphere inside the kiln, control the heating rate to 12℃ / min, raise the kiln temperature to 600℃, and pyrolyze at 600℃ for 2.5h. The volatile gases produced by pyrolysis are led to the combustion chamber after the rotary kiln for incineration.

[0066] Step S6: After pyrolysis, stop heating the rotary kiln and push the solid carbonized material at 600℃ into the sealed quenching discharge chamber at the tail of the rotary kiln. Fully open the gas outlet valve of the heat-insulating high-pressure buffer tank and use the gas pressure difference of 0.40MPa in the tank to transport the pressurized mixed gas to the quenching discharge chamber. Form a gas phase jet through the atomizing nozzle and directly spray it onto the solid carbonized material bed. Control the contact time to 20 minutes. The generated tail gas is discharged into the combustion chamber. After the solid material is cooled to room temperature, it is discharged to obtain hydroxyapatite modified biochar.

[0067] Example 4:

[0068] This embodiment provides a method for preparing hydroxyapatite-modified biochar, including the following steps: Step S1: Add 1000 parts of deionized water and 120 parts of bamboo powder to a pressure-resistant stirred reactor with a heating jacket. Control the initial temperature of the system to 22°C. Add 18 parts of ammonium polyphosphate and 49 parts of calcium acetate in sequence. Turn on the mechanical stirring in the reactor and set the stirring speed to 200 r / min. Soak at a constant temperature of 22°C for 2.0 h.

[0069] Step S2: Add 80 parts of urea to the reactor, seal the reactor body and all exhaust valves; introduce a heat source into the reactor jacket, control the heating rate to 2.0℃ / min, raise the temperature of the slurry in the reactor to 108℃, and stir at 108℃ for 2.5h. During this closed heating process, an absolute pressure of 0.18MPa is formed and maintained inside the reactor.

[0070] Step S3: Stop the heating of the reactor jacket, fully open the pneumatic pressure relief valve at the top of the reactor, and simultaneously start the steam jet compressor connected to the pipeline. Introduce 0.7MPa of motive steam as the injection source, and control the pressure inside the reactor to drop to 0.1MPa within 4s. The mixed gas discharged from the reactor pressure relief is drawn in by the ejector and mixed with the motive steam. The mixed fluid is pressurized to an absolute pressure of 0.35MPa. The pressurized mixed gas is discharged into the heat-insulated high-pressure buffer tank for sealed buffering. The internal temperature of the heat-insulated high-pressure buffer tank is controlled at 150℃ by electric heating.

[0071] Step S4: Discharge the slurry from the bottom of the reactor after treatment and pump it into an industrial plate and frame filter press for solid-liquid separation. Press the filter cake until the moisture content reaches 45% to obtain the wet precursor material.

[0072] Step S5: Feed the wet precursor material into the rotary kiln, introduce nitrogen to maintain an oxygen-free atmosphere inside the kiln, control the heating rate to 10℃ / min, raise the kiln temperature to 550℃, and pyrolyze at 550℃ for 2.0h. The volatile gases produced by pyrolysis are led to the combustion chamber after the rotary kiln for incineration.

[0073] Step S6: After pyrolysis, stop heating the rotary kiln and push the solid carbonized material at 550℃ into the sealed quenching discharge chamber at the tail of the rotary kiln. Fully open the gas outlet valve of the heat-insulating high-pressure buffer tank and use the gas pressure difference of 0.35MPa in the tank to transport the pressurized mixed gas to the quenching discharge chamber. Form a gas phase jet through the atomizing nozzle and directly spray it onto the solid carbonized material bed. Control the contact time to 15 minutes. The generated tail gas is discharged into the combustion chamber. After the solid material is cooled to room temperature, it is discharged to obtain hydroxyapatite modified biochar.

[0074] Comparative Example 1: Compared with Example 1, the difference is that in step S1, ammonium polyphosphate is not added, but is replaced with diammonium hydrogen phosphate with an equal molar amount of phosphorus. All other aspects are the same.

[0075] Comparative Example 2: Compared with Example 1, the difference is that urea is not added in step S2, and the closed heating and pressure holding operation is not performed. Instead, 25% ammonia water is directly added dropwise to the reactor under normal pressure to adjust the pH value of the system to 9.0. After stirring for 2.5 hours, the subsequent solid-liquid separation is carried out directly. Step S3 is omitted, and the rest are the same.

[0076] Comparative Example 3: Compared with Example 1, the difference is that in step S3, the pneumatic pressure relief valve at the top of the reactor is not opened, and the steam jet compressor is not used. Instead, the reactor is controlled to cool down and depressurize naturally in a closed state to room temperature and pressure, and then the exhaust is directly discharged and subsequent solid-liquid separation is carried out. The rest are the same.

[0077] Comparative Example 4: Compared with Example 1, the difference is that calcium acetate is not added in step S1, but is replaced with calcium nitrate in an equal molar amount of calcium element, while the rest are the same.

[0078] Comparative Example 5: Compared with Example 1, the difference is that the gas phase jet impact activation operation in step S6 is omitted, and the solid carbonized material at 550°C is directly cooled to room temperature under the nitrogen protective atmosphere of the rotary kiln and then discharged. The mixed gas discharged by flash evaporation is treated as waste gas. All other aspects are the same.

[0079] Test Example 1: Test objective: By testing the phase composition and surface elemental chemical states of the samples, the differences between the examples and the comparative examples in terms of crystal growth state and surface functional group grafting are compared.

[0080] Test subjects: hydroxyapatite-modified biochar prepared in Example 1, modified biochar prepared in Comparative Example 3, and modified biochar prepared in Comparative Example 5.

[0081] Test steps: The solid sample to be tested was ground in an agate mortar and passed through a 200-mesh standard sieve. The powder that passed through the sieve was placed in a vacuum drying oven and dried at 60°C for 12 hours to remove surface adsorbed moisture.

[0082] The dried powder sample was placed on a quartz glass sample stage, the surface was flattened, and it was placed in an X-ray diffractometer for phase testing. The test conditions were Cu target Kα rays, tube voltage was set to 40kV, tube current was set to 40mA, scanning range 2θ was set to 10°~80°, and scanning rate was set to 5° / min. The full spectrum data was acquired and recorded.

[0083] Another dried powder sample was uniformly pressed onto conductive adhesive and placed in the vacuum chamber of an X-ray photoelectron spectrometer for surface chemical state testing. The test conditions used a monochromatic Al Kα ray source, with the binding energy of C 1s (284.8 eV) as an internal standard for charge calibration. First, a full spectrum scan was performed with a binding energy range of 0–1200 eV, followed by a high-resolution narrow spectrum scan of N 1s in the range of 395–405 eV. The surface element content and peak area ratio of each chemical state were then derived.

[0084] The test data is shown in Table 1.

[0085] Table 1. Analysis data of phase composition and surface chemical state of Example 1 and Comparative Examples:

[0086] According to Table 1 and Figure 1 The test results show that Example 1 exhibits obvious characteristic diffraction peaks, with peak positions corresponding to the standard hydroxyapatite crystal phase. Combined with the data in Table 1, its calculated crystallinity is 71.4%. In contrast, the diffraction pattern of Comparative Example 3 shows a certain degree of peak broadening, a weakening of diffraction intensity, and a relatively lower crystallinity value. This difference indicates that, without the aid of a steam jet compressor for pressure relief, the physical pressure change of the reaction system during natural cooling and depressurization is relatively gradual. This may lead to a relatively slow release of dissolved ammonia and a small gradient in the pH value of the liquid phase, resulting in the inorganic phase nucleation process remaining in a low supersaturation range for a long period, thus affecting crystal development. The above phase test results demonstrate that negative pressure-induced flash evaporation has a certain promoting effect on the nucleation and crystallization process of hydroxyapatite.

[0087] Example 1 exhibits a distinct nitrogen characteristic peak at a specific binding energy position. Quantitative data in Table 1 show a total nitrogen content of approximately 4.82 at%, with the amino component accounting for 68.3% of the peak fitting. In contrast, Comparative Example 5 shows a relatively weaker signal intensity within the same binding energy range, indicating a lower total nitrogen content on the surface. This difference is presumably due to the omission of the jet impact operation with mixed gas in Comparative Example 5. Without in-situ impact of high-temperature water vapor and free ammonia on the solid carbon material, gas-phase thermal dissociation and chemical amination reactions on the carbon substrate surface are less likely to occur, thus affecting the grafting effect of nitrogen-containing functional groups at carbon framework defect sites.

[0088] The comprehensive characterization data of Example 1 demonstrate that the process design of the present invention can effectively achieve the expected physicochemical process. The high-temperature mixed gas stored in the preceding process serves as an activation medium in subsequent steps, which helps to introduce complexing groups for physicochemical adsorption onto the product surface.

[0089] Test Example 2: Test objective: To compare the differences in the degree of porous structure development between the examples and the comparative examples by measuring the nitrogen adsorption-desorption isotherms and pore parameters of different samples.

[0090] Test subjects: Hydroxyapatite-modified biochar prepared in Examples 1, 2, 3, and 4, and modified biochar prepared in Comparative Examples 3, 4, and 5.

[0091] Test steps: Take an appropriate amount of the solid sample to be tested and place it in a glass sample tube. Connect the sample tube to the degassing station and perform vacuum degassing pretreatment at a set temperature of 150℃ for 6 hours to completely remove the moisture and impurity gases adsorbed inside the pores of the material.

[0092] After degassing, the sample tube was transferred to the analysis station of the fully automated specific surface area and pore size analyzer. At a liquid nitrogen temperature of 77K, the relative pressure range was set from 0.01 to 0.99. High-purity nitrogen was gradually introduced into the sample tube for adsorption testing, and then the gas was gradually evacuated for desorption testing. The nitrogen adsorption amount data at different relative pressure points were recorded.

[0093] The measured isotherm data were processed using the instrument's accompanying analysis software. The specific surface area of ​​the sample was calculated using the BET multi-point method model, the micropore volume of the material was calculated using the t-plot method, and the total pore volume of the sample was calculated using the single-point adsorption data at a relative pressure of 0.99. The data were then exported and recorded.

[0094] The test data is shown in Table 2.

[0095] Table 2. Specific surface area and pore structure data of the examples and comparative examples:

[0096] According to Table 2 and Figure 2 The test results show that the modified biochar prepared in Example 1 exhibits the characteristics of a porous material in the nitrogen adsorption-desorption isotherm test. Figure 2 The isotherm trajectory shows that the adsorption amount of Example 1 increases rapidly in the low relative pressure range, which usually indicates the presence of a certain amount of microporous structure inside the solid. Specific test data in Table 2 show that the specific surface area of ​​Example 1 is 654.3 m². 2 The material exhibits a high density of nitrogen per gram (g) and a relatively high micropore volume, indicating a well-developed physical pore structure. In contrast, the nitrogen isothermal adsorption curves of Comparative Examples 3 to 5 show an overall downward trend, with all pore parameters decreasing to varying degrees.

[0097] For Comparative Example 4, due to the use of calcium nitrate as the calcium source, the internal expansion effect resulting from acetate decomposition and gas generation during the inert atmosphere pyrolysis stage may have been lacking, thus affecting the in-situ pore-forming process of the carbon substrate and leading to a lower pore volume. For Comparative Example 5, this batch omitted the mixed gas jet step, and the carbonized material lacked a chemical ablation reaction involving high-temperature water vapor during the cooling stage. The carbon framework structure did not undergo sufficient water-gas conversion consumption, resulting in a reduction in micropore volume and a decrease in specific surface area to 287.4 m². 2 / g. This data comparison illustrates that the external fluid vaporization activation process has a positive promoting effect on increasing the specific surface area of ​​the material.

[0098] Comparative Example 3 involved crystallization under natural cooling and depressurization conditions. The resulting hydroxyapatite particles may not have been uniform in size, and the relatively large inorganic particles adhered to the biomass channels, easily causing physical blockage. This, in turn, affected the entry of nitrogen molecules into the deeper layers of the material, leading to a decrease in the measured specific surface area. The combined test results of the above embodiments and comparative examples demonstrate that the pyrolysis gas-phase expansion step and the subsequent high-pressure gas-phase jet activation step in the process of this invention have a good synergistic effect in expanding the specific surface area of ​​the material and constructing a porous structure.

[0099] Test Example 3: Test objective: To measure the turbidity and calcium and phosphorus dissolution concentrations of the effluent under simulated industrial fixed-bed hydraulic shear conditions, and to compare the binding stability of the inorganic loading phase in the comparative examples and control examples.

[0100] Test subjects: Hydroxyapatite-modified biochar prepared in Example 1, Comparative Example 1, Comparative Example 2, and Comparative Example 3.

[0101] Test steps: Accurately weigh 10.0g of the solid sample to be tested, and uniformly pack it into a glass chromatography column with an inner diameter of 25mm. Fill both ends of the sample bed with an appropriate amount of degreased cotton to fix the bed.

[0102] Deionized water with an initial pH of 6.5 was used as the simulated flushing solution. The simulated flushing solution was continuously pumped into the glass chromatography column from bottom to top using a peristaltic pump. The empty bed flow rate on the liquid phase surface was controlled at 15 m / h, and the system was kept running continuously for 24 hours.

[0103] At 2h, 4h, 8h, 12h, 16h, 20h and 24h during the operation, effluent samples were collected at the outlet of the chromatography column, and the turbidity data of the effluent at each time point were measured and recorded using a portable turbidity meter.

[0104] Take 50 mL of the effluent collected at the end of 24 hours, add nitric acid and microwave digest it. Use inductively coupled plasma atomic emission spectrometry to determine the mass concentration of calcium and phosphorus in the digest. Combined with the initial elemental loading of the sample, calculate the cumulative loss rate of calcium and phosphorus within 24 hours.

[0105] The test data is shown in Table 3.

[0106] Table 3. Data on the resistance to hydraulic shear loss in the examples and comparative examples:

[0107] According to Table 3 and Figure 3 According to the test data, the modified biochar prepared in Example 1 exhibits relatively stable solid-phase retention characteristics under simulated fluid shear conditions. Figure 3The turbidity curve of the effluent in Example 1 changed relatively smoothly, remaining within a low range. The data in Table 3 show that the cumulative loss rate of calcium and phosphorus after 24 hours of continuous flushing was less than 1%. In contrast, the turbidity of each comparative example showed an increasing trend to varying degrees under the same water flow impact, and a higher concentration of calcium and phosphorus components was detected in the effluent, suggesting that the inorganic effective components may have undergone physical stripping and shedding from the carbon skeleton.

[0108] These data discrepancies reflect, to some extent, the impact of upstream process steps on the microstructure and bonding strength of the product. In Comparative Example 1, due to the absence of ammonium polyphosphate and the lack of macromolecular masking, conventional inorganic phosphates readily undergo heterogeneous reactions with calcium ions on the outer surface of the carbon skeleton. The resulting inorganic phase may aggregate on the external surface, making it easily physically stripped away under dynamic water flow. Comparative Example 2, by directly adding alkali to adjust pH, easily causes an imbalance in the local concentration gradient of the liquid phase, making it difficult for the inorganic phase to be effectively guided into the deep pore network of the material, thus affecting the bonding strength between the inorganic phase and the carbon skeleton. Comparative Example 3, crystallizing under natural cooling conditions, has a relatively slower nucleation rate, potentially resulting in larger inorganic particles that are difficult to fully contain by the micropores of the carbon substrate, making it difficult to form an ideal spatially confined structure during the subsequent high-temperature pyrolysis shrinkage stage.

[0109] Based on the above test results, the process design of this invention, through polymer coordination mechanisms, helps guide the precursor to penetrate into the deep structure of biomass. Combined with the transient pressure drop-induced crystallization and the skeletal shrinkage effect generated during pyrolysis, the target inorganic phase easily forms a relatively tight mechanical intercalation state within the biomass substrate.

[0110] Test Example 4: Test objective: To compare the differences in pollutant removal efficiency between the embodiment and the comparative example by measuring the equilibrium adsorption capacity and adsorption kinetics of the material for heavy metal ions in water.

[0111] Test subjects: hydroxyapatite-modified biochar prepared in Examples 1 to 4, and modified biochar prepared in Comparative Examples 1 to 5.

[0112] Test steps: Lead nitrate with an initial concentration of 500 mg / L was used to simulate heavy metal pollution in water. The initial pH of the water was adjusted to 5.0 using dilute nitric acid and sodium hydroxide solution.

[0113] Accurately weigh 0.05g of each solid sample to be tested and put them into conical flasks containing 50mL of the simulated water body, and seal the mouth of the flask.

[0114] The conical flask was placed in a constant temperature water bath shaker, and the temperature was set to 25℃ and the shaking speed was 150r / min to carry out the constant temperature adsorption reaction.

[0115] 1 mL of suspension was extracted at 10 min, 30 min, 60 min, 120 min, 240 min, 360 min and 480 min of reaction, and filtered through a microporous membrane with a pore size of 0.22 μm.

[0116] The mass concentration of lead ions in the filtrate was determined using a flame atomic absorption spectrometer. The adsorption amount at each time point and the equilibrium adsorption amount when the reaction reaches equilibrium were calculated based on the difference between the initial concentration and the residual concentration.

[0117] The test data is shown in Table 4.

[0118] Table 4. Equilibrium adsorption capacity and removal rate of lead ions in the examples and comparative examples:

[0119] According to Table 4 and Figure 4 The test results show that the example group exhibited good adsorption performance in the treatment test of heavy metal polluted water. Table 4 data shows that the equilibrium adsorption capacity for lead ions in Examples 1 to 4 all reached over 450 mg / g. Combined with... Figure 4 The adsorption kinetic curves show that Example 1 exhibits a relatively rapid adsorption rate in the initial stage of the reaction, gradually reaching a stable equilibrium state. In contrast, the equilibrium adsorption amounts of each comparative example show varying degrees of decrease, with Comparative Example 5 showing the lowest equilibrium adsorption amount. This test result suggests that the omission of certain process steps has a negative impact on the heavy metal ion removal efficiency of the final product.

[0120] These discrepancies in the data may be related to the physical and chemical structural characteristics of the materials during the adsorption process. For Comparative Examples 1 and 2, the uneven loading of the inorganic phase or agglomeration on the outer surface of the carbon substrate may reduce the number of effective active sites capable of chemical precipitation and ion exchange with heavy metal ions, thus affecting the overall chemical adsorption capacity of the materials. For Comparative Example 3, the relatively large inorganic crystals formed under natural conditions may, to some extent, block the fluid transport channels of the biochar, increasing the mass transfer resistance of heavy metal ions in the water to diffuse into the deep porous network of the carbon framework, making it difficult for some internal adsorption sites to fully function.

[0121] The reduced adsorption capacity in Comparative Examples 4 and 5 further reflects the positive effect of pore-forming and surface modification steps on improving material performance. Comparative Example 4, lacking a gas-phase expansion pore-forming process, has relatively limited micropore volume providing physical retention space. Comparative Example 5, by omitting the mixed gas jet impact, may lack the high specific surface area physical structure resulting from water-gas activation, and the carbon surface may also lack sufficient nitrogen-containing complex functional groups for grafting. This may limit the material's opportunity to undergo surface complexation reactions with heavy metal ions via Lewis acid-base interactions. In summary, the above test results indicate that the entire process of this invention exhibits good synergistic effects in constructing a well-developed porous network, fixing the precipitated active phase, and grafting surface complex groups, which is beneficial for achieving a comprehensive improvement in the material's environmental purification performance.

[0122] While specific embodiments of the present invention have been described above, those skilled in the art should understand that these specific embodiments are merely illustrative. Those skilled in the art can omit, substitute, and modify the details of the above methods and systems in various ways without departing from the principles and essence of the present invention. For example, combining the above method steps to perform substantially the same function and achieve substantially the same result using substantially the same method falls within the scope of the present invention.

Claims

1. A method for preparing hydroxyapatite-modified biochar, characterized in that, Includes the following steps: S1. Mix deionized water, biomass, ammonium polyphosphate and calcium acetate, and stir and impregnate under constant temperature to obtain impregnation slurry; S2. Add urea to the impregnation slurry and perform a heating and pressure holding treatment under closed conditions to form and maintain an absolute pressure in a slightly positive pressure state within the reaction system. S3. Depressurize the reaction system after pressure holding treatment, and simultaneously introduce power steam for negative pressure suction to reduce the pressure in the reaction system to atmospheric pressure. Then, pressurize the extracted mixed gas and send it to a heat-insulated high-pressure buffer tank for sealed constant temperature buffering. S4. Discharge the bottom slurry in the depressurized reaction system and perform solid-liquid separation to obtain wet precursor material; S5. The wet precursor material is heated and carbonized in an oxygen-free atmosphere to obtain a solid carbonized material. S6. The solid carbon material is placed in a sealed discharge chamber, and a mixed gas containing ammonia and water vapor, which was extracted, discharged and pressurized in step S3, is introduced. The solid carbon material is directly sprayed through a gas-phase jet to perform quenching and activation treatment. After cooling, hydroxyapatite modified biochar is obtained.

2. The method for preparing hydroxyapatite-modified biochar according to claim 1, characterized in that, In steps S1 and S2, the raw materials, by mass parts, include: 800-1200 parts of deionized water, 100-150 parts of biomass, 15-30 parts of ammonium polyphosphate, 25-50 parts of calcium acetate, and 60-100 parts of urea.

3. The method for preparing hydroxyapatite-modified biochar according to claim 2, characterized in that, The biomass is any one of pine sawdust, bamboo powder, corn stalks, or rice straw; The ammonium polyphosphate is a linear, water-soluble inorganic polymer with a degree of polymerization in the range of 20 to 50.

4. The method for preparing hydroxyapatite-modified biochar according to claim 1, characterized in that, Step S1 further includes: The initial temperature was controlled at 20-25℃, the stirring speed was set at 150-250 r / min, and the constant temperature soaking time was 1.5-2.5 h. The addition ratio of ammonium polyphosphate and calcium acetate satisfies the requirement that the molar ratio of calcium to phosphorus in the system is 1.60:1 to 1.70:

1.

5. The method for preparing hydroxyapatite-modified biochar according to claim 1, characterized in that, Step S2 further includes: Control the heating rate to 1.5–2.5℃ / min, raise the slurry temperature to 105–110℃, and stir at a constant temperature of 105–110℃ for 2.0–3.0 hours; The absolute pressure of the micro-positive pressure state is 0.15 to 0.20 MPa.

6. The method for preparing hydroxyapatite-modified biochar according to claim 1, characterized in that, Step S3 further includes: A motive steam pressure of 0.6–0.8 MPa is introduced as an ejector source to control the pressure in the reaction system to drop to an absolute pressure of 0.1 MPa within 3–5 seconds; The mixed gas from the intake and exhaust is mixed with the motive steam and then pressurized to an absolute pressure of 0.30–0.40 MPa. The internal temperature of the insulated high-pressure buffer tank is controlled within the range of 145-155℃ by electric heating.

7. The method for preparing hydroxyapatite-modified biochar according to claim 1, characterized in that, Step S4 further includes: Solid-liquid separation is carried out using a plate and frame filter press, and the filter cake is pressed until the moisture content reaches 40% to 50%.

8. The method for preparing hydroxyapatite-modified biochar according to claim 1, characterized in that, Step S5 further includes: Nitrogen gas is introduced to maintain an oxygen-free atmosphere inside the kiln. The heating rate is controlled at 8-12℃ / min, and the temperature is raised to 500-600℃. The kiln is then kept at a constant temperature of 500-600℃ for 1.5-2.5 hours. The volatile gases produced by the pyrolysis are then directed to the post-combustion chamber for combustion.

9. The method for preparing hydroxyapatite-modified biochar according to claim 1, characterized in that, Step S6 further includes: The mixed gas with an absolute pressure of 0.30 to 0.40 MPa in the heat-insulated high-pressure buffer tank is transported to the sealed discharge chamber, and the solid carbonized material bed is sprayed through the atomizing nozzle to form a gas phase jet, and the contact time is controlled to be 10 to 20 minutes.

10. The application of hydroxyapatite-modified biochar prepared by any one of claims 1 to 9 in water pollution control agents.